Autosomal recessive primary microcephaly type 2 associated with a novel WDR62 splicing variant that disrupts the expression of the functional transcript - Chen, Haizhu; Zheng, Ying; Wu, Hua; Cai, Naiqing; Xu, Guorong; Lin, Yi; Li, Jin-Jing (Frontiers in Neurology, 2024)
Background Autosomal recessive primary microcephaly (MCPH) is a rare neurodevelopmental disorder characterized primarily by congenital microcephaly and intellectual disability but without extra-central nervous system malformations. This investigation aimed to elucidate the genetic underpinnings of microcephaly in a patient from a Chinese consanguineous family. Methods A comprehensive clinical assessment, including brain magnetic resonance imaging (MRI), electroencephalogram (EEG), and genetic analyses, was conducted to evaluate the patient’s condition. Whole-exome sequencing (WES) was employed to identify the causative gene, followed by Sanger sequencing, to confirm the mutation and its segregation within the family. Reverse transcript polymerase chain reaction (RT-PCR) was utilized to detect changes in splicing. Western blot was employed to reveal the difference of protein expression level between the wild-type and mutant WDR62 in vitro. Results The patient exhibited classic MCPH symptoms, including microcephaly, recurrent epilepsy, delayed psychomotor development, and intellectual disability. Additionally, asymmetrical limb length was noted as a prominent feature. MRI findings indicated reduced brain volume with cortical malformations, while EEG demonstrated heightened sharp wave activity. A molecular analysis uncovered a novel homozygous variant c.4154–6 C > G in the WDR62 intron, and a functional analysis confirmed the pathogenicity of this mutation, resulting in the formation of an abnormal transcript with premature termination codons. Conclusion This study enhances our understanding of the genetic heterogeneity associated with MCPH and highlights the pivotal role of genetic testing in the diagnosing and managing of rare neurodevelopmental disorders. Furthermore, it highlights the potential of emerging genetic therapies in treating conditions such as MCPH2.